Comparison of fixed dose reduced-intensity conditioning with fludarabine and busulfan to PK-guided busulfan AUC (FluBu4K) in hematopoietic stem cell transplant for AML/MDS. Issue 4 (21st March 2021) - Rasor, Brendan; Dickerson, Tyler; Zhao, Qiuhong; Elder, Patrick; Brammer, Jonathan E.; Larkin, Karilyn; Jaglowski, Samantha; Mims, Alice; Penza, Sam; Vasu, Sumithira; Wall, Sarah A.; William, Basem; et al.
Abstract: A retrospective cohort study was conducted to assess differences in efficacy and tolerability between a busulfan AUC target of 16.4 mg × Hr/L per day (FluBu4K) and a conventional RIC regimen (FluBu2). Adult patients with a diagnosis of AML or MDS who received fludarabine + busulfan conditioning with or without antithymocyte globulin between 2015 and 2018 were included. The primary outcome was relapse free survival. Overall, 74 patients received conditioning with either FluBu4K or FluBu2. At 18 months, relapse-free survival was not significantly different, at 63.9% with FluBu4k compared to 57.5% with FluBu2 ( p = 0.49). There was a statistically significant difference in the cumulative incidence of relapse at 18 months in favor of the FluBu4K regimen, at 12.0% vs 32.5% ( p = 0.047). The results of this study indicate that for select patients, there may be benefit in choosing targeted FluBu4K over FluBu2. Adverse effects other than mucositis were not significantly different.